Pharmacotherapy of pulmonary hypertension (according to the 2015 ESC/EAS Guidelines for the diagnosis and treatment of pulmonary hypertension) - E. L. Trisvetova; S. V. Gubkin (Столичная издательская компания, 2016)
Indications and efficacy of drugs used for the treatment of pulmonary hypertension are considered. Stages of the treatment of pulmonary arterial hypertension are discussed, including maintenance therapy, specific therapy with calcium channel blockers, prostacyclin analogues, endothelin receptor antagonists, phosphodiesterase-5 inhibitors, prostacyclin agonists, guanylate cyclase stimulators, combination treatment.